2005
DOI: 10.1038/sj.jcbfm.9600248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Duration of Osmotherapy on Blood–Brain Barrier Disruption and Regional Cerebral Edema after Experimental Stroke

Abstract: Osmotherapy is the cornerstone of medical management for cerebral edema associated with large ischemic strokes. We determined the effect of duration of graded increases in serum osmolality with mannitol and hypertonic saline (HS) on blood-brain barrier (BBB) disruption and regional cerebral edema in a well-characterized rat model of large ischemic stroke. Halothane-anesthetized adult male Wistar rats were subjected to transient (2-h) middle cerebral artery occlusion (MCAO) by the intraluminal occlusion techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 30 publications
5
57
3
1
Order By: Relevance
“…This finding could be exploited diagnostically in attempts to assess the relative volumes of the central part and border zone of the ischemic lesion, given the availability of a ligand that binds selectively to the perivascular pool of AQP4. Our findings are in agreement with a recent study (15) which shows that osmotherapy with 7.5% hyperosmotic saline at 24 hr after MCAO in rats leads to a significant decrease in the brain water content in the cortical border zone (where the perivascular AQP4 expression is retained) but not in the central part of the lesion (where the perivascular AQP4 expression is strongly reduced).…”
Section: Discussionsupporting
confidence: 83%
“…This finding could be exploited diagnostically in attempts to assess the relative volumes of the central part and border zone of the ischemic lesion, given the availability of a ligand that binds selectively to the perivascular pool of AQP4. Our findings are in agreement with a recent study (15) which shows that osmotherapy with 7.5% hyperosmotic saline at 24 hr after MCAO in rats leads to a significant decrease in the brain water content in the cortical border zone (where the perivascular AQP4 expression is retained) but not in the central part of the lesion (where the perivascular AQP4 expression is strongly reduced).…”
Section: Discussionsupporting
confidence: 83%
“…In well-characterized animal models of ischemic stroke, institution and maintenance of a hyperosmolar state with continuous intravenous (IV) HS infusion ameliorates cerebral edema and improves survival [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…There is abundance of literature that supports the conventional theory of action of osmotic agents. Their potent anti-edema action is attributed to be primarily on undamaged brain regions with an intact blood-brain barrier (BBB), theoretically causing egress of water from the interstitial and extracellular space into the intravascular compartment, resulting in improved intracranial elastance [3][4][5][6][7][8][9][10][11]. In addition, osmotic agents have been shown to exert beneficial non-osmotic cerebral effects, such as augmentation of regional cerebral blood flow (CBF) resulting in enhanced tissue oxygen delivery, free radical scavenging, and modulation of cerebrospinal fluid formation and reabsorption [3][4][5][6][7][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Data from a study have indicated the maximum of BBB permeability at 48 h after brain injury [35]. In the present study, BBB permeability (vasogenic edema) was evaluated at 48 h post-trauma.…”
Section: Discussionmentioning
confidence: 99%